OPTIMAL TRACKING AND REGULATION ACCURACY OF FEEDBACK CONTROL SYSTEMS - BAKHTIAR, T. (School of Data Science, Mathematics and Informatics, IPB University, 2005)
This paper deals with intrinsic performance limits achievable by feedback control. We give analytical expressions of the optimal tracking and regulation problems for linear shift- invariant single-input and multiple-output (SIMO) discrete-time systems. For the former, we modify the existing results by means of the delta operator and show that the continuous-time counter- part results can be properly recovered from this point. For the latter, we derive a discrete-time result ﬁrst and show the conver- gence property.